2020
DOI: 10.3390/ijerph17010329
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the PLAYTOD Program on Children’s Physical Activity at Preschool Playgrounds in a Deprived Urban Area: A Randomized Controlled Trial

Abstract: Interventions to improve children’s physical activity in Early Childhood Education and Care (ECEC) settings are needed. This randomized controlled trial examines the effects of a preschool-based playground program for ECEC teachers in a deprived urban area. On intervention preschools, the PLAYgrounds for TODdlers program (PLAYTOD) was performed. It focused on teacher’s knowledge and skills in order to create a challenging outdoor environment in which young children (2.5 to 4 years old) are able to practice the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
4
0
1
Order By: Relevance
“…Our findings are consistent with scientific evidence from the literature demonstrating the positive effect of PA on improving motor and pre-literacy skills in preschool age (Orton et al, 2009;Logan et al, 2012;Zeng et al, 2017;Aivazidis et al, 2019;Popovic et al, 2020). Indeed, although the literature regarding the practice of PA in kindergarten is limited, recent researches have investigated the effects of different PA interventions on several skills and health aspects in preschoolers (Popovic et al, 2020;Toussaint et al, 2020). In 2008, Stodden et al developed a conceptual model hypothesizing a primary connection between the level of PA and the quality of MC (Stodden et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with scientific evidence from the literature demonstrating the positive effect of PA on improving motor and pre-literacy skills in preschool age (Orton et al, 2009;Logan et al, 2012;Zeng et al, 2017;Aivazidis et al, 2019;Popovic et al, 2020). Indeed, although the literature regarding the practice of PA in kindergarten is limited, recent researches have investigated the effects of different PA interventions on several skills and health aspects in preschoolers (Popovic et al, 2020;Toussaint et al, 2020). In 2008, Stodden et al developed a conceptual model hypothesizing a primary connection between the level of PA and the quality of MC (Stodden et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Observations on playgrounds also showed that, after PLAYTOD, the observed role of ECEC teachers on intervention playgrounds was more active. The results of the observations on playgrounds were recently published [23].…”
Section: Discussionmentioning
confidence: 99%
“…It focussed on the teachers' knowledge and practices in order to create a challenging outdoor environment in which young children can practice their motor skills. A detailed description of the intervention was previously published [20,23]. In short, 2 face-to-face training sessions of 2 hours each were organised for 4 groups of ECEC teachers.…”
Section: Study Sample and Recruitmentmentioning
confidence: 99%
“…Este hecho destaca que el enriquecimiento lúdico-motor del patio de recreo ha fomentado un comportamiento activo e interactivo de los niños. Sobre este tema, varios estudios de intervención con un diseño cuasi-experimental reportan un aumento significativo en el nivel de actividad física de los niños después de la introducción de materiales y marcas visuales en el patio de la escuela (Blaes et al, 2013;Erwin, Ickes, Ahn & Fedewa, 2014;Fairclough, Stratton & Butcher, 2008;Lopez et al, 2018;Ridgers et al, 2007;Stratton y Mullan, 2005;Toussaint et al, 2020;Verstraete, Cardon, Clercq & Bourdeaudhui, 2006). Además, Dowda y sus colegas ( 2009), al analizar la influencia del contexto escolar en los niveles de actividad física del niño, concluyeron que los niños en edad preescolar con niveles más altos de actividad física moderada e intensa asistieron a contextos escolares con las siguientes características en comparación con otros:…”
Section: Discussionunclassified